A REQUIREMENT MODEL OF A WEB-BASED DIARY STUDY FOR QUALITATIVE STUDIES (Journal of Digital System Development, 2023)
The Web-Based Diary Studies for Qualitative Studies aims to improve qualitative research by providing a comprehensive and user-friendly platform for conducting diary studies. This system uses web technology to record participants' thoughts, experiences, and activities over an extended period. The goal is to provide researchers with a valuable tool for efficiently and effectively collecting qualitative data in a longitudinal and context-rich manner. The system captures realtime user behaviour and experiences and gives researchers deep insights into user interactions and preferences. Several commercial diary study applications are available, and several studies apply the dairy study method in their data collection. However, they should have covered the design aspect of this app. Therefore, this paper aims to create a requirement model for qualitative studies' web-based diary study. This study was conducted using the Rapid Application Development methodology, where its prototype is evaluated in terms of usability using a survey method. Participants responded positively to the web-based diary study system, expressing satisfaction with its utility, user-friendliness, and overall performance. Most participants regarded the system as straightforward for conducting qualitative research. Furthermore, they commended the system's user-friendly interface and effective data management capabilities. This web-based platform empowers researchers to understand users' perspectives comprehensively and enables them to make informed decisions based on rich qualitative data. Overall, this system contributes to advancing the field of qualitative research by providing a robust and flexible tool for studying user experiences and behaviours over time.